(untitled) (Conferencea, 2024)
The article describes the issue of depreciation calculation for the main means used in the production of agricultural products. In particular, opinions, approaches and suggestions on improving the calculation of depreciation for perennial plants used in the production of agricultural products on the basis of international standards have been formulated.